Treatment of Petroleum Refinery Wastewater by Sono Fenton Process Utilizing the in-Situ Generated Hydrogen Peroxide - Jiad, Marwa M.; Abbar, Ali H. (Al-Khwarizmi Engineering Journal, 2023)
Combining ultrasonic irradiation and the Fenton process as a sono-Fenton process, the chemical oxygen demand (COD) in refinery wastewater was successfully eliminated using response surface methodology (RSM) with central composite design (CCD). The impact of two main influential operational parameters (iron dosage and reaction time) on the COD removal from wastewater generated by an Iraqi petroleum refinery facility was explored. Removal of 85.81% was attained under the optimal conditions of 21 minutes and 0.289 mM of concentration. Additionally, the results revealed that the concentration of has the highest effect on the COD elimination, followed by reaction time. The high R2 value (96.40%) validated the strong fit of the model equation and the successful adopting RSM in the treatment of wastewaters from petroleum refineries. Furthermore, a comparison among sono-Fenton, sono-Fenton with addition of externally, classical Fenton and sonolysis processes showed that the combined process of sono-Fenton is better than individual processes and the external addition of .